A food-grade expression system for d-psicose 3-epimerase production in Bacillus subtilis using an alanine racemase-encoding selection marker - Chen, Jingqi (Bioresour Bioprocess, 2017)
BACKGROUND: Food-grade expression systems require that the resultant strains should only contain materials from food-safe microorganisms, and no antibiotic resistance marker can be utilized. To develop a food-grade expression system for d-psicose 3-epimerase production, we use an alanine racemase-encoding gene as selection marker in Bacillus subtilis. RESULTS: In this study, the d-alanine racemase-encoding gene dal was deleted from the chromosome of B. subtilis 1A751 using Cre/lox system to generate the food-grade host. Subsequently, the plasmid-coded selection marker dal was complemented in the food-grade host, and RDPE was thus successfully expressed in dal deletion strain without addition of d-alanine. The selection appeared highly stringent, and the plasmid was stably maintained during culturing. The highest RDPE activity in medium reached 46 U/ml at 72 h which was comparable to RDPE production in kanamycin-based system. Finally, the capacity of the food-grade B. subtilis 1A751D2R was evaluated in a 7.5 l fermentor with a fed-batch fermentation. CONCLUSION: The alanine racemase-encoding gene can be used as a selection marker, and the food-grade expression system was suitable for heterologous proteins production in B. subtilis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40643-017-0139-7) contains supplementary material, which is available to authorized users.